Role of TIM-1 in the development and treatment of tumours - Cao, Jinmeng; Qing, Jilin; Zhu, Liya; Chen, Zhizhong (Frontiers in Cell and Developmental Biology, 2024)
T-cell immunoglobulin and mucin structural domain 1 (TIM-1, also known as hepatitis A virus c ell receptor 1) is a co-stimulatory molecule that is expressed predominantly on the surface of T c ells. TIM-1 promotes the activation and proliferation of T cells, cytokine secretion, and can also be overexpressed in various types of cancer. Upregulation of TIM-1 expression may be associate d with the development and progression of cancer. After reviewing the literature, we propose that TIM-1 affects tumour development mainly through two pathways. In the Direct pathway: overex pression in tumours activates tumour-related signaling pathways, mediates the proliferation, apop tosis, invasion and metastasis, and directly affects tumour development directly. In the indirect p athway: In addition to changing the tumour microenvironment and influencing the growth of tum ours, TIM-1 binds to ligands to encourage the activation, proliferation, and generation of cytokin es by immune cells. This review examines how TIM-1 stimulates the development of tumours in direct and indirect ways, and how TIM-1 is exploited as a target for cancer therapy.